Cattle gastrointestinal nematode egg-spiked faecal samples: high recovery rates using the Mini-FLOTAC technique - Amadesi, Alessandra (Parasit Vectors, 2020)
BACKGROUND: Faecal egg count (FEC) techniques are commonly used to detect gastrointestinal nematodes (GINs) in cattle and to determine anthelmintic efficacy/resistance through the faecal egg count reduction test (FECRT). Mini-FLOTAC is one of the techniques recommended for a standardised FEC/FECRT of helminth eggs in cattle. However, only one paper evaluated the recovery rate of GIN eggs by Mini-FLOTAC (compared to McMaster and modified-Wisconsin method) in cattle, using only a level of contamination of 200 eggs per gram (EPG) of faeces and using GIN eggs collected from goat faeces to spike faecal samples from cattle. To further study the recovery rate of GIN eggs from cattle faeces, this study was conducted in two laboratories, one in Belgium and one in Italy to evaluate the sensitivity, accuracy, precision and reproducibility of the Mini-FLOTAC and McMaster techniques (at two reading levels: grids and chambers) for the detection of GIN eggs in spiked bovine faecal samples. METHODS: In both countries, spiked cattle faecal samples with five different levels of egg contamination (10, 50, 100, 200 and 500 EPG) of GINs were used. The study was performed in both laboratories by the same expert operator and using the same standard operating procedures (SOPs) for the Mini-FLOTAC and McMaster techniques. Sensitivity, accuracy and precision were calculated for each technique and for each level of contamination. Statistical analyses were performed to evaluate differences in performance between the two techniques. RESULTS: Mini-FLOTAC had a higher sensitivity (100% at all EPG levels for Mini-FLOTAC vs 0–66.6% for McMaster chambers and grids at levels< 100 EPG), a higher accuracy (98.1% mean value for Mini-FLOTAC vs 83.2% for McMaster grids and 63.8% for McMaster chambers) and a lower coefficient of variation (10.0% for Mini-FLOTAC vs 47.5% for McMaster grids and 69.4% for McMaster chambers) than McMaster. There was no significant difference in the recovery of GIN eggs between the two studies performed in Belgium and in Italy. CONCLUSIONS: The high GIN egg recovery rate detected by Mini-FLOTAC and the similar results obtained in Belgium and in Italy indicated that the diagnostic performance of a FEC technique was not dependent on the laboratory environment. [Image: see text]